Răspuns :
................................................................................
![Vezi imaginea C04f](https://ro-static.z-dn.net/files/da6/ea7a972d48ecd61ca36ef7ce46f2ab84.jpg)
Este o formula foarte simpla pentru asta:
(x1+x2+x3)²-2(x1x2+x1x3+x2x3)
Formulele sunt:
x1+x2+x3 = -b supra a
x1x2+x1x3+x2x3 = c supra a
Deci o sa arate in felul urmator: (-b/a)²-2(c/a)
Acum obtinem: (-b/a)² => -(+3) supra 1 = -3/1 = (-3)² = -3 ori -3 = +9
c/a => -1/1 = -1:1 = -1
Acum o sa arate in felul urmator: 9 - 2(-1) => 9 - (-2) = 9+2= 11
(x1+x2+x3)²-2(x1x2+x1x3+x2x3)
Formulele sunt:
x1+x2+x3 = -b supra a
x1x2+x1x3+x2x3 = c supra a
Deci o sa arate in felul urmator: (-b/a)²-2(c/a)
Acum obtinem: (-b/a)² => -(+3) supra 1 = -3/1 = (-3)² = -3 ori -3 = +9
c/a => -1/1 = -1:1 = -1
Acum o sa arate in felul urmator: 9 - 2(-1) => 9 - (-2) = 9+2= 11